Tracing the Underpricing Trail: The Impact of Debt to Asset Ratio and Inflation in IPO - Jufri Yandes (International Journal of Economics and Management Research, 2024)
This study investigates whether Debt to Asset Ratio and inflation have an impact on underpricing in Indonesia during 2021-2022. This study uses two statistical methods, namely the classical assumption test and multiple regression, to test the hypothesis. This study uses secondary data from the Indonesia Stock Exchange, with a total sample of 112 companies. Of these, 75 companies fulfilled the specified criteria and were selected as research samples. The results showed that the Debt to Asset Ratio partially affects underpricing in 2021-2022. However, the Inflation variable has no effect on underpricing. It is suspected that the Debt to Asset Ratio affects stock underpricing because investors rely on this information when buying IPO shares. Conversely, people do not consider inflation as a major factor in investment decisions which ultimately affects the level of underpricing. This study only finds empirical evidence of the effect of Debt to Asset Ratio (DAR) on underpricing, although many studies have discussed the relationship between DAR, inflation, and underpricing. The empirical findings of this study can contribute to future research for issuing companies and researchers, with a particular focus on aspects such as financial risk, inflation rate, and the underpricing phenomenon.